2006
DOI: 10.1521/suli.2006.36.6.709
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Notes in Mexico: What Do They Tell Us?

Abstract: According to international and Mexican official statistics, there is a dramatic rise in suicide in Mexico; however, research in this area is severely limited. This is the first study of suicide notes from Mexico in the international literature. From a population of 747 registered suicides, a sample of 106 note-writers and 106 non-note writers was examined. Using the demographic (descriptive) scheme of Ho, Yip, Chiu, and Halliday (1998), the results indicate that note writers do not differ greatly from other su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 12 publications
3
21
0
1
Order By: Relevance
“…The reality is that suicide notes are relatively uncommon in the United States and their absence does not indicate anything systematic about the suicide or the decedent. While this study was conducted in one U.S. state, studies of suicide notes in other cultures have yielded disparate and conflicting results about frequency, content, and meaning of notes (e.g., Chavez‐Hernandez, Paramo, Leenaars, & Leenaars, ; Demirel, Akar, Sayin, Candansayar, & Leenaars, ; Haines, Williams, & Lester, ; Wong, Yeung, Chan, Yip, & Tang, ). In addition, a note may not be as meaningful or helpful as many suicide bereaved may wish.…”
Section: Discussionmentioning
confidence: 99%
“…The reality is that suicide notes are relatively uncommon in the United States and their absence does not indicate anything systematic about the suicide or the decedent. While this study was conducted in one U.S. state, studies of suicide notes in other cultures have yielded disparate and conflicting results about frequency, content, and meaning of notes (e.g., Chavez‐Hernandez, Paramo, Leenaars, & Leenaars, ; Demirel, Akar, Sayin, Candansayar, & Leenaars, ; Haines, Williams, & Lester, ; Wong, Yeung, Chan, Yip, & Tang, ). In addition, a note may not be as meaningful or helpful as many suicide bereaved may wish.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversy still exists on whether differences do exist between letter writers and non letter writers. Although some studies found few differences (Chavez-Hernandez, Paramo, Leenaars et al, 2006;Foster, 2003;Girdhar, Leenaars, Dogra et al, 2004;Leenaars, 2004), others found that letter writers were more likely to be young, female, use more lethal suicide methods (e.g., charcoal burning, hanging, or poisoning) and were less likely to have mental and physical illness, previous suicide attempts, or drug addictions (Chia & Tsoi, 1979;Ho, Yip, Chui et al, 1998;Kuwabara, Shiori, Nishimura et al, 2006;O'Connor, Sheehy, & O'Connor, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…Ho, Yip, Chiu, and Halliday (1998) developed the most widely used classification scheme, with data being obtained from police records, demographic data, and suicide notes. A similar classification scheme has been used in India (Girdhar, Leenaars, Dogra, Leenaars, & Kumar, 2004) and in Mexico (Chavez‐Hernandez, Paramo, Leenaars, & Leenaars, 2006), and we use a similar scheme in this study. However, the data in these studies are not entirely consistent and differences in collection occur among researchers.…”
mentioning
confidence: 99%
“…However, the data in these studies are not entirely consistent and differences in collection occur among researchers. Comparisons of note writers with non‐note writers, and differences in demographic features like age and sex, have failed to yield consistent results (Chavez‐Hernandez et al, 2006; Foster, 2003; Girdhar et al, 2004; Ho et al, 1998; Salib, El‐Nimr, & Yacoub, 2002).…”
mentioning
confidence: 99%